Respon Waktu Pemangkasan Pucuk Pada Masa Vegetatif dan Dosis NPK 16-16-16 Terhadap Produksi Benih Tanaman Kenikir (Cosmos sulphureus) - Wardana, Bima Oktasa Dwi; Azizah, Maria; Saleh, Ismail (Agropross : National Conference Proceedings of Agriculture, 2023)
Kenikir (Cosmos sulphureus) is a local plant that is often found both in the yard of the house or open land, so it is generally used as an ornamental plant. However, in fact this plant has a myriad of benefits, including as a traditional vegetable which has the effect of increasing appetite, anti-cancer and anti-inflammatory stomach; natural dyes, edible flowers, ornamental plants, weed and pest control. Of the many benefits, the kenikir plant is a multipurpose plant, so it is necessary to carry out continuous development and cultivation processes. Unfortunately, this is inversely proportional to the availability of plant material to reproduce plants, namely seeds. Innovations that can be made to increase seed production are pruning techniques and NPK 16-16-16 nutrients. The purpose of this study was to determine the effect of pruning time and application of NPK 16-16-16 nutrients on the seed production of marigolds. This research was conducted for 5 months starting from October 2022 to February 2023 in Tegalwaru, Mayang, Jember Regency. The experimental design was arranged in a factorial randomized block design with 3 replications. The first factor was pruning time which consisted of 3 levels (P1: 3 MST, P2: 4 MST, and P3: 5 MST) and the second factor was the dosage of NPK 16-16-16 fertilizer consisting of 3 levels (F1: 10 g, F2: 15 g, and F3: 20 g NPK pearl planting). The results showed that pruning time had a highly significant effect on the number of branches parameter at 5 MST treatment level, and the dose of npk 16-16-16 had a highly significant different effect on the parameter number of fertilized flowers at a dose of 15 grams, and had a significantly different effect on number of branches with a dose of 20 grams.